Panoramic snapshot of serum soluble mediator interplay in pregnant women with convalescent COVID-19: an exploratory study - Fernandes, Geraldo Magela; Sasaki, Lizandra Moura Paravidine; Jardim-Santos, Gabriela Profírio; Schulte, Heidi Luise; Motta, Felipe; da Silva, Ângelo Pereira; de Carvalho, Aleida Oliveira; Pereira, Yacara Ribeiro; Alves, Caroline de Oliveira; de Araújo Júnior, David Alves; Mendonça-Silva, Dayde Lane; Costa, Karina Nascimento; et al. (Frontiers in Immunology, 2023)
This prospective observational study designed to characterize the immunological status of pregnant women with convalescent COVID-19 focused on a snapshot of the interplay among serum soluble mediators. A sample of 141 pregnant women from all prenatal periods (1st, 2nd and 3rd trimesters) comprised patients with convalescent SARS-CoV-2 infection at 3-20 weeks after the onset of symptom (COVID, n=89) and a control group of pre-pandemic non-infected pregnant women (HC, n=52). Chemokine, pro-inflammatory/regulatory cytokine and growth factor levels were quantified by a high-throughput microbeads array. In the HC group, most serum soluble mediators progressively decreased towards the 2nd and 3rd trimesters of pregnancy, while higher chemokine, cytokine and growth factor levels were observed in the COVID patient group. Serum soluble mediator signatures and heatmap analysis pointed out that the major increase observed in the COVID group related to pro-inflammatory cytokines (IL-6, TNF-a, IL-12, IFN-g and IL-17). A larger set of biomarkers displayed an increased COVID/HC ratio towards the 2nd (3x increase) and the 3rd (3x to 15x increase) trimesters. Integrative network analysis demonstrated that HC pregnancy evolves with decreasing connectivity between pairs of serum soluble mediators towards the 3rd trimester. Although the COVID group exhibited a similar profile, the number of connections was remarkably lower throughout the pregnancy. Meanwhile, IL-1Ra, IL-10 and GM-CSF presented a preserved number of correlations (≥5 strong correlations in HC and COVID), IL-17, FGF-basic and VEGF lost connectivity throughout the pregnancy. IL-6 and CXCL8 were included in a set of acquired attributes, named COVID-selective (≥5 strong correlations in COVID and <5 in HC) observed at the 3rd pregnancy trimester. From an overall perspective, a pronounced increase in serum levels of soluble mediators with decreased network interplay between them demonstrated an imbalanced immune response in convalescent COVID-19 infection during pregnancy that may contribute to the management of, or indeed recovery from, late complications in the post-symptomatic phase of the SARS-CoV-2 infection in pregnant women.